A Principle of Neuromechanical Matching for Motor Unit Recruitment in Human Movement. Issue 3 (July 2019) - Hudson, Anna L.; Gandevia, Simon C.; Butler, Jane E.
Abstract : What determines which motor units are active in a motor task? In the respiratory muscles, motor units are recruited according to their mechanical advantages. We describe a principle of motor unit recruitment by neuromechanical matching due to mechanisms in the spinal cord that sculpt descending drive to motoneurons. This principle may be applicable to movements in nonrespiratory muscles. Abstract : A novel principle of motor unit recruitment by neuromechanical matching for human movement control.